UTILITY OF COARSE GRAINS AS SUPERFOODS (International Journal of Food and Nutritional Sciences, 2022)
Based on grain size, coarse grains are divided into two parts. The first coarse grains include jowar and millet. Second, small grains include coarse grains with very small grains like ragi, kangni, kodo, cheena, sawa, kutki, etc. Cultivation of millets has many advantages like drought tolerance, short duration of crop maturity, low cost due to minimum requirement of fertilizers, manures, and disease resistance to fight against pests. These grains can be grown even in less water and barren land and in adverse weather. Salhar, Kang, Jowar, Maize, Madiya, Kutki, Sawa, Kodo, etc. if compared with wheat for protein, fat, mineral content, fiber, carbohydrate, energy calorie, calcium, phosphorus, iron, carotene, folic acid, zinc and amino acid If done with grains like rice, they cannot be underestimated in any way. According to the Gazette of India, on April 13, 2018, millets (jowar, bajra, ragi, etc.) have great potential to contribute to the nutritional security of the country. Thus, millets are not only a storehouse of nutrients, but they are also climate-resilient crops and have wonderful nutritional properties. Thus, present paper deals utility of coarse grain as superfood.